2021
DOI: 10.1016/j.isci.2021.103450
|View full text |Cite
|
Sign up to set email alerts
|

Neurogenic-dependent changes in hippocampal circuitry underlie the procognitive effect of exercise in aging mice

Abstract: Summary We have shown that the improvement in hippocampal-based learning in aged mice following physical exercise observed is dependent on neurogenesis in the dentate gyrus (DG) and is regulated by changes in growth hormone levels. The changes in neurocircuitry, however, which may underlie this improvement, remain unclear. Using in vivo multimodal magnetic resonance imaging to track changes in aged mice exposed to exercise, we show the improved spatial learning is due to enhan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 75 publications
1
7
0
Order By: Relevance
“…Given previous findings relating neuron density, MD, and ISOVF to cognitive abilities, one may expect B6 mice in our cohort to have poor memory performance. In mice, higher neuron density in the BLA is associated with improved CFM performance ( Yang et al, 2008 ), and neurogenesis-driven decreases in MD track spatial learning improvements during a related active place avoidance paradigm ( Zhou et al, 2021 ). Additionally, higher cortical neuron counts in mice have been associated with better perceptual discrimination ( Fang and Yuste, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Given previous findings relating neuron density, MD, and ISOVF to cognitive abilities, one may expect B6 mice in our cohort to have poor memory performance. In mice, higher neuron density in the BLA is associated with improved CFM performance ( Yang et al, 2008 ), and neurogenesis-driven decreases in MD track spatial learning improvements during a related active place avoidance paradigm ( Zhou et al, 2021 ). Additionally, higher cortical neuron counts in mice have been associated with better perceptual discrimination ( Fang and Yuste, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…As yet, no study probed the effects of exogenous EST on rsFC in men. There is some evidence that changes in rsFC of the hippocampus depend on hippocampal neurogenesis in female mice 76 . However, previous studies 77 , 78 on hippocampal neurogenesis did not detect significant EST effects in male rats, either, and suggest an androgen-dependent mechanism, but it is unclear whether and how altered neurogenesis translates to altered rsFC in humans.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the improvement in hippocampal-based learning in aged mice after physical exercise is dependent on neurogenesis in the dentate gyrus and is regulated by growth hormone level changes. Specific changes in hippocampal circuitry underlying the cognitive improvements resulting from physical activity were also identified, suggesting dependency on neurogenesis activation in aged animals (Blackmore et al, 2021;Zhou et al, 2021). Cheng et al (2020) observed that treadmill exercise promotes neurogenesis and myelin repair by upregulating the Wnt/β-catenin signaling pathway and improves the neurological deficit caused by focal cerebral ischemia/ reperfusion.…”
Section: Promotion Of Neurogenesismentioning
confidence: 97%